INTERNATIONALIZATION OF EDUCATION REFORM AND MANAGEMENT OF HIGHER EDUCATION: THE GERMAN MODEL - Zinchenko, Viktor V. (Educological discourse, 2016)
Internationalization and integration of institutions of higher education in a global and international dimension raise many new questions for the theory and practice. Among them the author emphasizes the most important ones: what is the general and the particular in education and science; what patterns, forms, methods of management are universal and which are in the range of the specific conditions of different countries; what is the best way to realize the functions of education and science in the international activity; what are the features of national identity in education and in the development of the University as an institution of education, and also in organizational behavior, management systems; to what extent these features are important to achieve the desired results; how can foreigners quickly adapt to national environment.